Electronic interface board to monitor and control CERN´s sputter ion pump - Roda, Marco André Felício (2017)
This report presents the work developed during the master internship at the European Organization for Nuclear Research (CERN). The described work resulted from two initial objectives: improvement of the control system of vacuum sectors and the development of a new Pro bus-DP intelligent slave interface board for sputter ion pump controllers. Since the objectives were distinct, the work was split into two di erent projects. In the rst project, the control system for vacuum sectors of Large Hadron Collider, Super Proton Synchrotron and Complex Proton Synchrotron was improved. A new control rmware based in VHDL was developed, tested and upgraded for the control cards. The second project presented in this report involved the development of an electronic card for sputter ion pump controllers. Currently, the communication between the Pro bus network and the ion pump controllers is performed by a remote input-output station based on the ET200 module from Siemens. The operation and status information of the ion pumps and their controllers provided to the network are limited since the remote input-output station does not acquire all the available signals. Moreover, the physical connections between the remote input-output station and each ion pump controller is done with a dedicated cable, which is prone to connection malfunctions. In order to reduce the complexity, improve the signal integrity and upgrade the monitoring and control of the ion pumps system, a new Pro bus-DP intelligent slave interface was developed. It aims to provide direct Pro bus connection to the ion pump controller and to give to the Pro bus master access to all its control signals, improving the controllers usability and exibility. In this report, the card topology, its internal modules, the rmware, the LabVIEW application and assessment tests are presented and described.